Existential security: Preparatory School Students - الحركاني فوز فاضل (lark, 2020)
Abstract :- The present research aims at identifying the existential security of the preparatory stage students and the statistical differences in the existential security of the preparatory stage students according to gender variable (male, female), grade (fourth, fifth) and specialization (scientific, literary). To achieve this, the researcher adopted the existential security measure, which consists of (28) paragraphs, and was presented to a group of arbitrators to judge the validity of paragraphs, and extracted psychometric characteristics of him through its application to the research sample (400) students from the preparatory stage were selected by random stratified method The researcher verified the stability of the scale in two ways: retest and the coefficient of stability (0.83), and using the Alphakronbach equation (0.80) has reached the results that the middle school students have a low level of existential security, males are better than Female in existential security, there is no Us is statistically significant for variable grade and specialization .